Phylogeny, genetic diversity and phylogeography of the genus Codoma (Teleostei, Cyprinidae). (8th September 2014) - Schonhuth, Susana; Lozano‐Vilano, Lourdes; Perdices, Anabel; Espinosa, Héctor; Mayden, Richard L.
<x xml:space="preserve">Abstract</x> This study represents a thorough analysis of Codoma, a monotypic genus endemic to north‐western Mexico. A previous morphological analysis of the species concluded that there exists several morphological groups in Codoma ornata, suggesting diversity in Codoma could be underestimated. No studies have examined the genetic diversity in Codoma ornata to test this hypothesis and identify independent lineages. We present a phylogeographic analysis using one mitochondrial and two nuclear genes, and specimens from across nine major drainages in both the Chihuahuan Desert and the Sierra Madre Occidental of western Mexico. All genes and analyses recovered populations of Codoma in a well‐supported clade and sister to Tampichthys, and this clade sister to Cyprinella. Analyses of both mitochondrial and nuclear genes indicated Codoma is not monotypic and recover more diversity in the genus than currently recognized. The four (mitochondrial) and five (nuclear) genetically distinct lineages are consistent with those groups outlined in the prior morphological study of the genus. Composition and distribution of these major lineages is also consistent with prior biogeographic hypothesis for other fishes in the region, supporting an ancestral Rio Grande system extending south towards central Mexico. Fragmentation of this paleosystem was followed by allopatric speciation in the Chihuahuan Desert. These results suggest a scenario of long‐term isolation in four major regions (upper Conchos, lower Conchos, Nazas, upper Mezquital). Resolution of the diversity and biogeography of these lineages has many implications for various biological disciplines, especially for evolutionary and conservation studies.